The Same Bond at Different Prices: Identifying Search Frictions and Selling Pressures - Feldhütter, Peter (Review of Financial Studies, 2012)
[I propose a new measure that identifies when the market price of an over-the-counter traded asset is below its fundamental value due to selling pressure. The measure is the difference between prices paid by small traders and those paid by large traders. In a model for overthe-counter trading with search frictions and periods with selling pressures, I show that this measure identifies liquidity crises (i.e., high number of forced sellers). Using a structural estimation, the model is able to identify liquidity crises in the U.S. corporate bond market based on the relative prices paid by small and large traders. New light is shed on two crises, the downgrade of General Motors and Ford in 2005 and the subprime crisis.]